Current state of populations and resources of Salvia stepposa in Central Kazakhstan - Butumbayeva М.К.; Silanteva М.М.; Turzhanova, S.S.; Nortseva М.А.; Turlybekova, G.K. (Fundamental and Experimental Biology, 2022)
World experience in the use of medicines shows the prospect of developing drugs based on the use of plant raw materials, including wild-growing ones. In thisaspect, field studies are needed to assess the status of medicinal plant populations to organize a system ofrational use and conservation of biological diversity. For Salvia stepposapopulations, we evaluate botanical features, ontogenetic spectrum, and resource indicators of plants. Structural indicators of four populations of S. stepposa in the Ulytau, Karkaraly Mountains, Spassky Hills, and Korneev forests are studied. It is determined that the species composition of communities ranged from 25 to 44 species. Populations in the Ulytau and Karkaraly Mountains are defined as young by the ratio of ontogenetic groups; populations in the Korneev forests and Spassky Hills — as medium-aged. All populations are in satisfactory condition and can be used to organize preparations of medicinal plant raw materials. The total area of the studied thickets in the Karaganda region amounted to 45.4 hectares, the yield varied from 284 to 462 kg/ha. The final operating reserve is estimated at 16,677 kg, the volume of possible collection is 8339 kg.